2011
DOI: 10.1371/journal.pone.0027511
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Ras Requires the ERM-Dependent Link of Actin to the Plasma Membrane

Abstract: BackgroundReceptor tyrosine kinases (RTKs) participate in a multitude of signaling pathways, some of them via the small G-protein Ras. An important component in the activation of Ras is Son of sevenless (SOS), which catalyzes the nucleotide exchange on Ras.Principal FindingsWe can now demonstrate that the activation of Ras requires, in addition, the essential participation of ezrin, radixin and/or moesin (ERM), a family of actin-binding proteins, and of actin. Disrupting either the interaction of the ERM prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 45 publications
1
55
0
Order By: Relevance
“…3). It is becoming increasingly apparent that all three ERM proteins can modulate the activity of the Ras superfamily of small GTPases, including the Ras and Rho subgroups, by interacting with their guanine exchange factors (GEFs) and guanine nucleotide dissociation inhibitors (GDIs), which are vital for their activation (Sperka et al, 2011;Takahashi et al, 1997;Valderrama et al, 2012). Ras is a molecular switch that is important for RTK-dependent activation of the MAP kinase pathway, such as through EGFR and HGFR (Easty et al, 2011;Orian-Rousseau et al, 2007;Ridley et al, 1995).…”
Section: Erm Proteins In Cancer Progressionmentioning
confidence: 99%
See 1 more Smart Citation
“…3). It is becoming increasingly apparent that all three ERM proteins can modulate the activity of the Ras superfamily of small GTPases, including the Ras and Rho subgroups, by interacting with their guanine exchange factors (GEFs) and guanine nucleotide dissociation inhibitors (GDIs), which are vital for their activation (Sperka et al, 2011;Takahashi et al, 1997;Valderrama et al, 2012). Ras is a molecular switch that is important for RTK-dependent activation of the MAP kinase pathway, such as through EGFR and HGFR (Easty et al, 2011;Orian-Rousseau et al, 2007;Ridley et al, 1995).…”
Section: Erm Proteins In Cancer Progressionmentioning
confidence: 99%
“…ERM proteins have been proposed to be responsible for a new step in Ras activation in that they are recruited to F-actin and co-receptors, specifically to receptors involved in cell adhesion, such as b1 integrin and CD44, at the plasma membrane in response to activation of RTKs. In doing so, ERM proteins can form a complex that acts as a scaffold and binds both GDP-bound Ras and the N-terminal region of the GEF son of sevenless homolog (SOS) (Sperka et al, 2011). Ezrin has specific binding domains for CD44, Ras and the autoinhibitory Dblhomology-pleckstrin-homology (DH-PH) domain of SOS but only after ezrin is in a complex with F-actin and its co-receptor can it bind to the DH-PH domain of SOS and expose the allosteric binding site that is specific for GDP binding of Ras (Sperka et al, 2011).…”
Section: Erm Proteins In Cancer Progressionmentioning
confidence: 99%
“…This is highly relevant given that EZR together with radixin and/or moesin form ERM complexes that connect actin to other membrane proteins (Sperka et al 2011). Sperka et al (2011) showed that activation of RAS requires the essential participation of ERM complexes and actin and that disrupting either the interaction of the ERM proteins with co-receptors or by downregulation of ERM proteins abolished growth factor-induced RAS activation.…”
Section: Proteomic Analysismentioning
confidence: 99%
“…This is highly relevant given that EZR together with radixin and/or moesin form ERM complexes that connect actin to other membrane proteins (Sperka et al 2011). Sperka et al (2011) showed that activation of RAS requires the essential participation of ERM complexes and actin and that disrupting either the interaction of the ERM proteins with co-receptors or by downregulation of ERM proteins abolished growth factor-induced RAS activation. The NGFinduced neuronal differentiation initiates a signal cascade requiring activation of RAS signaling, and interfering interference with the activity or function of RAS has been shown to impede or abolish NGF-induced differentiation (Klesse et al 1999, Sperka et al 2011.…”
Section: Proteomic Analysismentioning
confidence: 99%
See 1 more Smart Citation